Fungsi Internal Audit dan Manajemen Risiko Perusahaan: Sebuah Tinjauan Literatur - Balqis Nagita Fillia Zunaedi; Hayyu Rachma Annisa; Murdiyati Dewi (Jurnal Bisnis dan Akuntansi, 2022)
In this qualitative study, it became clear that an evolution towards a higher level of risk-based auditing is absolutely necessary, if internal auditors are to play an important role in risk management. The implementation of effective risk management is the key to the success of a company. This article aims to provide a literature review related to the role of the internal auditor function in carrying out effective and efficient risk management. The explanation of this article can add to the literature related to the role of internal auditors in implementing corporate risk management and can assist company management in selecting internal auditors so that company goals can be achieved. Thus, the company can have an optimal level of risk according to the company's risk appetite. Internal auditors are also required to uphold the professional standards of internal audit in carrying out their duties so as to provide the best guarantee for the company.